Seberapa Efektivitas Aplikasi SiAKU Terhadap Laporan Keuangan Koperasi Desa Wisata Candirejo: Studi Kasus Pada Koperasi Desa Wisata Candirejo - Rizka Yunifia Putri; Widhian Hardiyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the difference in how effective and efficient the application is in managing the financial statements of the Candirejo Tourism Village Cooperative, before and after using through the Financial Administration Information System (SiAKU) application. Through the Si AKU application, experts provide comprehensive updates and settings to make it easier for Candirejo city tourists to help record visit packages. Candirejo tourism village is a tourism located in Candirejo Village, Borobudur District, Magelang Regency, Central Java Province. This study used quantitative procedures with data collection strategies through convenience surveys to obtain satisfaction fulfillment scores. This study uses quantitative methods that explain the differences between variables. This study used a sample of 10 respondents from employees of the Candirejo Tourism Village Cooperative through the interview method and the Paired T-Test stage with an alpha of 5%. The results of this test show that there are differences between effectiveness and efficient variables in managing the time of making financial statements at the Candirejo Tourism Village Cooperative.